Clear and present danger - Clancy, Tom, 1947-2013 Jr., (Thomas Leo) (New York : Berkley Books, 1989)
The assassinations of U.S. ambassador and the visiting head of the F.B.I. by Colombian drug lords trigger a mysterious covert response and an investigation of U.S. and Colombian actions by Jack Ryan.
Keywords: Ryan, Jack (Fictitious character) -- Fiction; Clark, John (Fictitious character) -- Fiction; Spy stories; Intelligence service -- United States -- Fiction; Suspense fiction, American; Novela estadounidense; Novela de suspenso